Multi-objective Simulated Annealing for Dynamic Economic/Emission Dispatch - Ziane, Ismail; Graa, Amel; Benhamida, Farid; Salhi, Yacine; Bendaoud, Abdelber (2015 North American Power Symposium (NAPS), 2015)
This paper presents a Simulated Annealing (SA) Optimization to solve a Dynamic Economic/Emission Dispatch problem (EED). In this work, the problem is formulated as a multi-objective with two competing functions, namely economic cost and emission functions, subject to different constraints. The inequality constraints considered are the generating unit capacity limits while the equality constraint is generation-demand balance. To show the advantages of the proposed algorithm, it has been applied for solving multi-objective EED problems in a 6-generators system considering NO x , SO 2 , and CO 2 emission. This technique is compared with other techniques which reveals the superiority of the proposed approach and confirms its potential for solving other power systems problems.